2012
DOI: 10.1172/jci62812
|View full text |Cite
|
Sign up to set email alerts
|

CD2AP in mouse and human podocytes controls a proteolytic program that regulates cytoskeletal structure and cellular survival

Abstract: CD2AP in mouse and human podocytes controls a proteolytic program that regulates cytoskeletal structure and cellular survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…Together, these data provide direct support for our original hypothesis that dendrin is a CatL transcription factor and that its ability to induce CatL expression requires loss of CD2AP. 2 Granted, overall CatL staining, although similar to our published results, is generally less pronounced. 2 Difference in signal intensity is most likely due to different antibodies used, since Weins et al 1 used commercially available anti-CatL antibody (Sigma Aldrich) whereas we used polyclonal antibody specifically raised to detect cytoplasmic CatL.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Together, these data provide direct support for our original hypothesis that dendrin is a CatL transcription factor and that its ability to induce CatL expression requires loss of CD2AP. 2 Granted, overall CatL staining, although similar to our published results, is generally less pronounced. 2 Difference in signal intensity is most likely due to different antibodies used, since Weins et al 1 used commercially available anti-CatL antibody (Sigma Aldrich) whereas we used polyclonal antibody specifically raised to detect cytoplasmic CatL.…”
supporting
confidence: 90%
“…2 Furthermore, we and others have shown that appearance of cytoplasmic CatL leads to the loss of dynamin 3 and synaptopodin 4 due to proteolysis, which in turn results in reorganization of the actin cytoskeleton in podocytes.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…15 As inferred from interventions involving CD2AP protein and the cation channel TRPC6, both components of the slit diaphragmpodocyte cell junction protein complex, signals emanating from podocyte cell junctions may induce calcineurin-dependent cathepsin L-mediated degradation of critical structural and cytoskeletal proteins in podocytes. 15,16 This process is assisted by TGF-b-dependent translocation of dendrin from slit diaphragm-cell junction complexes to nuclei and subsequent transcription and expression of cathepsin L. 15 Because mutations of several components of the slit diaphragm-podocyte cell junction complex cause FSGS, 1,2 it seems possible that cathepsin L-mediated intracellular proteolysis induced by dysfunctional slit diaphragm-podocyte cell junction signaling is a common mechanism for podocyte abnormalities in FSGS. Considering that foot process effacement predates disease-associated podocyte sickness and death, could it be possible that the dysfunctional signaling becomes sustained and eventually, causes uncontrolled proteolysis?…”
mentioning
confidence: 99%
“…In the cytosol, cleavage of dynamin, synaptopodin and CD2AP by cathepsin L in renal podocytes leads to cytoskeletal reorganization and triggers the breakdown of the glomerular filtration barrier in a mouse model of proteinuric kidney disease [22][23][24] . Furthermore, the presence of endogenous cathepsin L inhibitors in the nucleus suggests some degree of regulation of cathepsin L activity in this compartment 25,26 .…”
mentioning
confidence: 99%